The use of machine translation in developing the writing skill of university students studying in the Arabic language department - Airussham, Nurul Syafiqah; Mohd. Ismath, Nurul Hanilah (USIM Press, 2022)
This research aims to identify the importance of using machine translation in developing the writing skill, and to identify the extent to which university students studying in the Arabic language department can rely on the use of machine translation in writing. The researcher used the quantitative and qualitative analytical method to obtain information and data that would answer the research questions. The questionnaire was distributed electronically through Google Form, and 100 responses were obtained from the sample, who are students of the International Islamic University Malaysia from three departments of Arabic language and multiple colleges; It is the Department of Arabic Language for Global Communication from the College of Languages and Administration, the Department of Arabic Language and Literature from the College of Knowledge of Revelation, and the Department of Teaching Arabic as a Second Language from the College of Education. In collecting data related to the research objectives, the researcher used the questionnaire that was distributed to the respondents. In the process of analyzing the questionnaire, the researcher used the statistical analysis package for social sciences (SPSS) program in order to obtain the arithmetic mean and standard deviation for all items of the questionnaire. One of the most important results of the research was that machine translation is useful in the lives of students, and there is no doubt that it has effectively helped in developing the writing skill of university students studying in the Department of Arabic Language, but it should have human intervention so that the translated sentences do not deviate from their true meanings. It is hoped that the research will be a reference for future researchers who are doing research on machine translation in the development of the four skills.